Pengaruh Manajemen Sumber Daya Pendidik dan Kepemimpinan Kepala Sekolah terhadap Mutu Sekolah di Madrasah Aliyah Swasta Yayasan Pondok Pesantren Babakan Jamanis Parigi Pangandaran - Ai Adah; Sri Rochani Mulyani; Farida Yuliaty (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2022)
Through this research, it is expected to obtain empirical evidence about the influence of Educator Resource Management and Principal Leadership on School Quality in Private Madrasah Aliyah, Babakan Jamanis Parigi Pangandaran Islamic Boarding School Foundation. The object of research in this research is Madrasah Aliyah Private Islamic Boarding School Foundation Parigi Pangandaran, because based on the observations of researchers that there is a phenomenon of educators who do not have an academic degree and there are still many who have not been certified. The research method used is descriptive and verification analysis with data collection techniques using questionnaires distributed to educators using total sampling technique (saturated) because the population is only 25 people. The results of descriptive analysis prove that educator resource management, principal leadership and quality the school is classified as very good, the results of the verification analysis "there is a strong positive relationship between educator resource management and principal leadership on school quality".